Phenomenological study of high energy exchanges based on multipheral ideas - Ferro Fontan, C.; Masperi, Luis; Page, R. (Societa italiana di fisica, 1972)
Fil: Ferro Fontan, C. Universidad de Buenos Aires; Argentina